ANALISA PERBANDINGAN SIFAT FISIS DAN MEKANIS ANTARA PENA PEMUKUL SS1-V1 BUATAN PINDAD DENGAN M16-A1 BUATAN AMERIKA - Oktosatrio, Suhendro; Sugihandoko; TjandraKusuma, Taufan (JURNAL MEKANIKASISTA, 2024)
This research analyzes the differences in physical and mechanical properties between the firing pin of the SS1-V1, manufactured by Pindad, and the firing pin of the M16-A1, manufactured in the United States. The main focus is to determine the cause of frequent damage to the SS1-V1 firing pin, while the M16-A1 firing pin does not experience similar issues. Testing included hardness tests, microstructure analysis, and material composition analysis, showing that although both pins have similar material structures, there are significant differences in composition and design. As a result, the author recommends changes in the composition, structure, and design of the SS1-V1 firing pin to make it stronger and more durable.